Application Of the Eigenface Method in The Presence System Using Web-Based Face Recognition: Study At E-learning Marketplace in Bandung - Darmawan, Fahrizal; Kusnandar, Toni; Fauka, Ahfi; Sudrajat, Adjat (Informatics Management, Engineering and Information System Journal, 2023)
The swift progress of technology has yielded numerous advantages, particularly for organizations engaged in vocational education, such as E-learning Marketplace in Bandung (Luarsekolah). One of the advantages of technology in vocational education is the use of attendance system technology. Luarsekolah's attendance system employs a conventional fingerprint recognition method, which frequently encounters difficulties when employees attempt to clock in, as their fingerprints are occasionally not acknowledged. Hence, creating a system that facilitates and streamlines employee attendance without requiring physical interaction is imperative. To address this, a facial recognition system utilizing the eigenface approach, with a development methodology based on the waterfall method, is suggested. Using the Eigenface PCA (Principal Component Analysis) technique, this system can function in real time. The research findings demonstrate the efficacy of the eigenface approach in real-time applications. The eigenface approach incorporates multiple validations to ensure the system's accuracy when employees utilize it. The approach incorporates several validations, such as presenting a message when an employee's face is near the camera and indicating a message when the employee's face is not directed toward the camera. If the camera misses adequate lighting, the system will automatically modify the lighting conditions to enable the camera to capture the employee's facial features.